2010
DOI: 10.1152/ajpheart.01021.2009
|View full text |Cite
|
Sign up to set email alerts
|

Sex-related resistance to myocardial ischemia-reperfusion injury is associated with high constitutive ARC expression

Abstract: The female sex has been associated with improved myocardial salvage after ischemia and reperfusion (I/R). Estrogen, specifically 17beta-estradiol, has been demonstrated to mediate this phenomenon by limiting cardiomyocyte apoptosis. We sought to quantitatively assess the effect of sex, ovarian hormone loss, and I/R on myocardial Bax, Bcl-2, and apoptosis repressor with caspase recruitment domain (ARC) expression. Male (n = 48), female (n = 26), and oophorectomized female (n = 20) rabbits underwent 30 min of re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 44 publications
1
18
0
1
Order By: Relevance
“…Further, in Tg(cmlc2:nucDsRed) zebrafish we found evidence of myocardial cell apoptosis and necrosis; at the 18 h time point, ∌10% of cardiomyocytes were TUNEL + and ∌15% of cardiomyocytes were necrotic as evidenced by AO staining. Both the time course and the magnitude of cell death observed in zebrafish are comparable to what has been shown to occur in the mammalian heart [29].…”
Section: Discussionsupporting
confidence: 70%
“…Further, in Tg(cmlc2:nucDsRed) zebrafish we found evidence of myocardial cell apoptosis and necrosis; at the 18 h time point, ∌10% of cardiomyocytes were TUNEL + and ∌15% of cardiomyocytes were necrotic as evidenced by AO staining. Both the time course and the magnitude of cell death observed in zebrafish are comparable to what has been shown to occur in the mammalian heart [29].…”
Section: Discussionsupporting
confidence: 70%
“…In a mouse model of acute MI, males have delayed myocardial healing, higher infarct re-expansion, and an increased risk of cardiac rupture [23]. In females, endogenous estrogens (biologically active 17-ÎČ-estradiol) have been demonstrated to aid in limiting cardiac apoptosis, thereby resulting in reduced infarct size in response to ischemia/ reperfusion injury [24,25]. While this is an area of intense ongoing investigation, estrogens may mediate a large portion of the observed sex differences in response to acute coronary ischemia and reperfusion.…”
Section: Burden Of Ischemic Heart Disease In Men and Women Prevalencementioning
confidence: 99%
“…ARC levels were also shown to drop following hypoxia/reoxygenation in cultured rat cardiomyocytes, a loss which can, however, be counteracted by repeated short post-conditioning cycles of hypoxia/reoxygenation [28]. Interestingly, a recent study conducted in rabbits suggested that endogenous levels of oestrogen mediate a constitutively higher ARC expression in the heart tissue of female individuals, which confers elevated apoptosis resistance in response to ischaemia/reperfusion and might explain the enhanced myocardial recovery of female individuals [29]. …”
Section: (Patho)physiology and Arc Expressionmentioning
confidence: 99%